2019
DOI: 10.4102/phcfm.v11i1.1982
|View full text |Cite
|
Sign up to set email alerts
|

Exploring resilience in family physicians working in primary health care in the Cape Metropole

Abstract: BackgroundDespite the high prevalence of burnout among doctors, studies have shown that some doctors who choose to remain in primary healthcare (PHC) survive, even thrive, despite stressful working conditions. The ability to be resilient may assist family physicians (FPs) to adapt successfully to the relatively new challenges they are faced with. This research seeks to explore resilience through reflection on the lived experiences of FPs who have been working in PHC.AimTo explore the resilience of FPs working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
4
0
2
Order By: Relevance
“…These themes form the components of the resilience conceptual model, as shown in Figure 2 . After we completed the meta-synthesis, we found a recently published relevant primary study [ 44 ]. We were able to incorporate its findings into our synthesis, which suggested that theoretical saturation had been reached.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These themes form the components of the resilience conceptual model, as shown in Figure 2 . After we completed the meta-synthesis, we found a recently published relevant primary study [ 44 ]. We were able to incorporate its findings into our synthesis, which suggested that theoretical saturation had been reached.…”
Section: Resultsmentioning
confidence: 99%
“…A possible limitation of the study includes the small number of primary studies that fit the inclusion criteria. However, the findings from a recent study published after the duration of the meta-synthesis produced consistent themes [ 44 ], suggesting a theoretical saturation and validity of the line-of-argument synthesis. Given the gravity of the situation, the next wave of research should focus on ways to reduce mental health problems and enhance resilience among physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of defined FM role within healthcare system A major limiting factor is the lack of a defined role of FM within the healthcare system. 10,21,24,35,41,46,56,57,65,[72][73][74][75][76][77][78] The key reasons for this were identified as a lack of career pathway, inappropriate deployment, and lack of critical mass to be visible within the healthcare system. Confusion over the role of FPs extended to policymakers, patients, other doctors, medical students and FPs.…”
Section: Dedicated Fps and Traineesmentioning
confidence: 99%
“…possuem menos cobrança consigo mesmo, comemorando sempre os pequenos ganhos diante dos resultados positivos de cada paciente. Além disso, aceitam as limitações do próprio serviço e tentam melhorar as suas condutas frente a algo negativo, por meio de sua própria iniciativa (Wagner;Pather, 2019). Portanto, percebe-se que a resiliência é multifatorial, pois propõe que o indivíduo se reinvente em meio a diversas situações vivenciadas pelo profissional da área da saúde.…”
Section: Introductionunclassified
“…Além disso, mediante o estudo da neurofisiologia, identifica-se que a resiliência é característica intrínseca de sistemas complexos, logo possui a capacidade de fornecer ao cérebro humano maiores habilidades para superar a perda de integridade e enfrentar problemas externos estressores. Por conseguinte, os estudos neurofisiológicos relacionados a resiliência, têm sido fundamentais para a descoberta de novas formas de habilidades e atitudes para o desempenho desse mecanismo (Wagner;Pather, 2019). Recentemente, houve a pandemia da COVID-19, onde foi possível perceve que os transtornos psiquiátricos identificados nos profissionais, possuem relação com o déficit de resiliência.…”
Section: Introductionunclassified